Design and Fabrication of a Solar Powered Sawdust Briquette Machine for Okra Preservation - Raphael O. BOLABORO; Matthew S. ABOLARIN; Henry I. MORKAH; Adeshola O. OPENIBO; Omotayo I. OGUNWEDE; Kafayat T. OBANIMOMO (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Storage of agricultural products is an ongoing problem in the agricultural sector with an all-round effect on the economy and other sectors. This research is aimed at reducing okra wastes due to lack of proper storage of the okra. The study focus is on how to improve the storage of okra by designing and fabricating a sawdust briquette powered cabinet dryer, capable of drying products at a regulated temperature and achieve efficient drying in lesser time with lesser contamination, while retaining the quality of the products after drying with solar powered Briquette machine. Sawdust was dried, carbonized and moulded to form briquette to serve as fuel for heating the dryer while a temperature regulator and a blower were incorporated in the design to aid the drying. The dryer has a capacity of 1.576 kg and results obtained from the performance evaluation carried out on the dryer showed that, it was able to dry okra to a desired moisture content of 10% within a period of 5 hours 30 minutes. The efficiency of the dryer was based on input and output of heat which was 70% using 0.22 kg of sawdust briquette in the dryer to dry the okra.